2018
DOI: 10.1097/med.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic role of iodine excess in loss of homeostasis in autoimmune thyroiditis

Abstract: To provide an overview of the studies conducted during the last few years implicating iodine in the development and manifestation of autoimmune thyroiditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…To begin with, a recent study found that carbonic anhydrase (CA) is genetically related to TgAb ( 47 ). Decreased CA activity may induce the production of TgAb via high levels of iodine uptake ( 48 ). CA is the main diver of hepatic gluconeogenesis and de novo lipogenesis by providing HCO3- for the first reaction ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…To begin with, a recent study found that carbonic anhydrase (CA) is genetically related to TgAb ( 47 ). Decreased CA activity may induce the production of TgAb via high levels of iodine uptake ( 48 ). CA is the main diver of hepatic gluconeogenesis and de novo lipogenesis by providing HCO3- for the first reaction ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies report no increase or a reduction in thyroid autoimmunity with time following fortification . The analysis of epidemiological data from a mildly iodine‐deficient population in Tasmania found no association between iodine supplementation and an increase of thyroid autoimmunity between 1995 and 2013 …”
Section: Thyroid Disorders Associated With Iodine Excessmentioning
confidence: 96%
“…However, other studies report no increase or a reduction in thyroid autoimmunity with time following fortification. 113,154,[156][157][158] The analysis of epidemiological data from a mildly iodinedeficient population in Tasmania found no association between iodine supplementation and an increase of thyroid autoimmunity between 1995 and 2013. 158 Improved diagnostic criteria and increasing the use of screening technologies for the thyroid (particularly thyroid ultrasound) have led to increased detection of mild thyroid disorders; this has likely contributed to an increase in the incidence of thyroid disorders and biased comparison over time.…”
Section: Hypothyroidismmentioning
confidence: 99%
See 2 more Smart Citations